Identify the Expressive Components of the Urban Landscape between the Experience of Virtual Environments and the Traditional Way: A Study of the Status of the Capital Sana'a - Al-Sorori, Maha Abdulrahman Shamsan; Al-Madhaji, Mohammed Ahmed Sallam (University of Science and Technology, Yemen, 2018)
The virtual environments have opened new horizons that represent new beginnings in identifying the expressive components that influence the urban scene. They have moved humans consciousness into a dynamic environment with continuous dynamic spaces that are electronically formed in a nonhuman way towards science fiction and diving away from the body, It is known that Yemeni people is still living on the margins of most modern technological developments and their response is limited with various planning and design processes and continues to follow traditional stereotypes because of the absence of scientific knowledge about the nature of virtual environments. The objective of this research is to establish a cognitive framework to clarify the concept of virtual environments and the components of the expressionistic landscape. This will be done by measuring the experience of virtual environments and comparing them with the traditional method. The statistical analytical approach to measure the experiment through theapplication of the center of the capital city of Sanaa - Ammanat Alasemah - Altahreer area - as a case of study to reach a set of conclusions andrecommendations that contribute to knowledge of the possibilities of virtual environments and their ability to recognize the expressive components in theurban landscape.